Identification of Supporting Architectural Ornaments of the Old City Semarang Site - Rohman Eko Santoso (Lembaga Pengembangan Kinerja Dosen, 2025)
The Old City of Semarang is an important part of the Semarang Old Town area, which is also designated as a Cultural Heritage Site. This area features distinctive European architecture that has adapted to the tropical climate of Semarang. This uniqueness gives the Old City buildings different characteristics and styles, depending on the period or year of construction. This study aims to explore and preserve the historical character of the Old City area by preserving supporting architectural elements, such as staircase ornaments and floor patterns. The research method uses descriptive qualitative analysis, by depicting the conditions in the field based on data obtained from observation and research. Overall, the results of this study show that the architectural elements of the supporting buildings in the Old City of Semarang reflect specific styles from different periods. In the 18th century, buildings in this area used the Rococo style. In the late 18th and early 19th centuries, Neo-Classical style was adopted. The early 19th and early 20th centuries saw the use of Neo-Renaissance style, while in the 20th century, the buildings in this area showed influences of modern architecture.